Polemik Bahasa Roh sebagai tanda awal baptisan Roh Kudus - Yanto Sutrisno; Gregorius Suwito; Gidion Gidion (Davar : Jurnal Teologi, 2023)
Abstract One of the main factors in church growth is the role of the power of the Holy Spirit in enabling humanity to respond to the preaching of the Gospel. However, to this day, there are still doubts in some church circles about the continuation of the power of the Holy Spirit as happened on the day of Pentecost, especially in the polemic "speaking in tongues as an initial sign of Spirit baptism". Researchers seek to bridge differences and build a comprehensive construction of teaching tongues for all groups, and benefit optimal growth of faith and fullness of the congregation. The method in this research is analysis with a qualitative approach which focuses on the problems of this biblical study on differences in the hermeneutical basis (interpretation) of texts, phrases and verses which cause differences in the teaching of tongues. The researcher concludes that speaking in tongues is an initial sign for believers who have received the baptism of the Holy Spirit, because this is the sign worn and experienced by the New Testament people in accordance with the fulfillment of God the Father's promise. The various works of the Holy Spirit which are described differently must be understood as a manifestation of cooperation between the person of the Holy Spirit and every believer.Keywords: Baptism of the Holy Spirit; Spirit-filled; The gift of the spirit; Tongues.AbstrakSalah satu faktor utama pertumbuhan gereja adalah peran kuasa Roh Kudus yang memampukan  umat manusia meresponi pemberitaan Injil. Namun hingga hari ini, masih ada keraguan sebagian kalangan gereja terhadap keberlanjutan kuasa Roh Kudus seperti yang terjadi di hari Pentakosta, khususnya dalam polemik “berbahasa roh sebagai tanda awal baptisan Roh”. Peneliti berupaya menjembatani perbedaan dan membangun sebuah konstruksi pengajaran bahasa roh yang komprehensif bagi semua kalangan, dan memberi manfaat pertumbuhan iman dan kepenuhan yang optimal dari jemaat. Metode dalam penelitian ini adalah analisis dengan pendekatan kualitatif yang memfokuskan kepada permasalahan studi biblika ini kepada perbedaan landasan hermeneutika (penafsiran) teks, frasa dan ayat yang menyebabkan perbedaan pengajaran bahasa roh. Peneliti menyimpulkan bahwa berbahasa roh adalah tanda awal bagi orang percaya yang telah menerima baptisan Roh Kudus, karena inilah tanda yang dikenakan dan dialami umat Perjanjian Baru sesuai penggenapan janji Allah Bapa. Ragam karya Roh Kudus yang digambarkan secara berbeda harus dipahami sebagai perwujudan kerjasama antara pribadi Roh Kudus dengan setiap orang percaya.Kata kunci: Baptisan Roh Kudus; Dipenuhi Roh; Karunia roh; Bahasa roh.